THE UIS MODEL FOR ONLINE SUCCESS - Bloemer, Bill (Online Learning, 2009)
This case study describes the philosophy underlying the delivery of online programs and courses at the University of Illinois – Springfield. The strategies used to implement the UIS model and the measures used to validate its success are outlined. These factors are reviewed in the context of the Sloan-C Five Pillars for quality learning environments.